The influence of personal factors and job satisfaction on marital quality among Muslim working women - Abdul Rahman, Soffizzan; Juhari, Rumaya; Yaacob, Siti Nor (2012)
Married women who work face various challenges in managing both sides of the world. Performing both tasks demand high degree of commitment and the responsibilities that need to be performed may vary across family life cycle. Success in one domain may influence the other. This study examined the relationships between personal factors, job satisfaction and marital quality among respondents from different stages of family life cycle. Participants were 235 married working women from four districts in Selangor, whose husbands residing together with them at the time of the study. Self-administered questionnaire was used for data collection. The results indicate that there are significant differences in marital quality and job satisfaction between the different stages of life cycle. Women who have more children, older, and have long-term marriage reported lower marital quality. It is also noted that higher educated women tend to have high marital quality while increased in job satisfaction would ensure a better quality marriage among the respondents. Future studies need to consider using longitudinal data to fully understand the impact of job satisfaction on marital quality across the life cycle.